POSITIVE LEADERSHIP – ATTEMPT TO CLARIFICATION AND ASSESSMENT OF NOVELTY - Zbierowski, Przemysław (Journal of Positive Management, 2017)
Purpose: The paper attempts to clarify the concept of positive leadership. Over the last decade a couple of models of positive leadership have been produced. The paper is purely conceptual its objective is to introduce some order and attempt to clarify what positive leadership really is. Methodology/approach: The method used in the paper is literature review. The main body of the paper presents three positive leadership concepts: fundamental state of leadership, authentic leadership and positive deviance. They are described and compared along with looking for similarities and causal relationships between them and former leadership concepts: transformational leadership and servant leadership. Findings: There are quite a few similarities and causal relationships between positive and former leadership concepts: self-awareness that is the fundamental issue in both authentic leadership and fundamental state of leadership is very closely linked to transformational leadership and servant leadership. Moreover, the whole concept of servant leadership is very close to positive way of organizing. Implications for future research: By introducing some order in the field of positive leadership the paper opens the space for future research that might more accurately address complex relationships of positive leaders. Value of the paper: Even though positive leadership has received some attention recently, this is the first paper to consider a variety of approaches and to underline the similarities, differences and possible causal relationships among them.